Effect of catalyst pore size on styrene production rate - Zeynali, Mohammad Ebrahim (Diffusion Fundamentals, 2010)
In this study the diffusion coefficients for reaction components were determined for unimodal and bimodal pore size distribution and assuming transitional diffusion regime using a more realistic, Stewart-Johnson, method. It was found that determination of diffusion coefficient using the average pore size results in underestimated values. A comparison was made between the effects of unimodal and bimodal pore size distribution on diffusion coefficients. The governing differential equation for a single pellet for styrene production was solved by orthogonal collocation method. The effectiveness factor which is a key parameter in reactor design was determined for the reaction in practical range of pore size. It was found that the production rate and effectiveness factor are sensitive to pore size and pore size distribution and with certain pore size distribution a considerable improvement in production rate can be achieved.